1989
DOI: 10.1063/1.343914
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of mass separation in a vacuum arc centrifuge

Abstract: A vacuum arc centrifuge is described which produces a rapidly rotating metal plasma column by means of the Lorentz force between the arc current and an applied axial magnetic field. Analysis of samples deposited on collector surfaces indicates mass separation of elements that i~crea~es with the radius. For the plasma formed from a brass cathode, the mass separation of zmc wl~h respect to copper depends on the configuration of the power supply and applied magnetic field and can exceed 50% at the outer radius of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In equation (7), any axial current flow in the steady rotation region of the centrifuge (after the grid) has been neglected. Rather than solve the problem in the entire driving region (including the cathode) a simple Gaussian form is assumed for the radial distribution of axial current just before the anode grid:…”
Section: Description Of Plasma Rotationmentioning
confidence: 99%
“…In equation (7), any axial current flow in the steady rotation region of the centrifuge (after the grid) has been neglected. Rather than solve the problem in the entire driving region (including the cathode) a simple Gaussian form is assumed for the radial distribution of axial current just before the anode grid:…”
Section: Description Of Plasma Rotationmentioning
confidence: 99%
“…But once uo = uoc, further increase in the power input only produces additional ionization. The more recent development utilizes a vacuum arc [17]- [20] to produce a fully ionized plasma, and in this way overcomes the AlfvCn limit. Fig.…”
Section: Plasma Centrifugementioning
confidence: 98%
“…A number of interesting papers have been published dealing with the laser-initiated vacuum arc plasma centrifuge, [17]- [20]. A fully ionized plasma is produced and transported through an axial magnetic field.…”
Section: Plasma Centrifugementioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of the vacuum arc centrifuge in 1981 (Krishnan et al 1981), various experimental and theoretical studies have been performed (Geva et al 1984, Prasad and Krishnan 1987a, Evans et al 1989, Del Bosco et al 1987. Research on plasma centrifuges reported since 1989 has been reviewed by Whichello et al (1994).…”
Section: Introductionmentioning
confidence: 99%